2021
DOI: 10.1002/mp.15046
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of 3D time‐reversal reconstruction of proton‐induced acoustic signals for dose verification in the head and the liver: A simulation study

Abstract: Purpose In vivo range and dose verification based on proton‐induced acoustics (protoacoustics) is potentially a useful tool for proton therapy. Built upon our previous study with two‐dimensional reconstruction, the time reversal (TR) method was extended to three‐dimensional (3D) and evaluated at two treatment sites (head and liver) through simulation, with the emphasis on a number of aspects such as increased spatial coverage, computational workload, and signal interference among slices. Methods Two mono‐energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Therefore, the BP position and relative dose can be inferred from the reconstruction of the initial pressure, whereas the absolute dose reconstruction requires an accurate knowledge of the medium properties (density and Grünensein parameter). Recent simulation studies have investigated the accuracy of ionoacoustics-based dose reconstruction for clinical scenarios using a linear array (van Dongen et al 2019) or sparse two and three dimensional sensor arrays positioned around the patient (Yu et al 2019(Yu et al , 2021. Assuming exact knowledge of the medium, they showed that the BP can be located with millimeter or sub-millimeter accuracy, depending on the proton pulse time profile.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the BP position and relative dose can be inferred from the reconstruction of the initial pressure, whereas the absolute dose reconstruction requires an accurate knowledge of the medium properties (density and Grünensein parameter). Recent simulation studies have investigated the accuracy of ionoacoustics-based dose reconstruction for clinical scenarios using a linear array (van Dongen et al 2019) or sparse two and three dimensional sensor arrays positioned around the patient (Yu et al 2019(Yu et al , 2021. Assuming exact knowledge of the medium, they showed that the BP can be located with millimeter or sub-millimeter accuracy, depending on the proton pulse time profile.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the accuracy will be increased if we create a dictionary of IA waves before the treatment to match the measured signals 22,31 . The use of multiple (or array‐type) sensors will further increase the accuracy as the three‐dimensional dose distributions can be obtained using iterative time‐reversal reconstruction methods 20,32,33,34 . Particularly, a novel array OH sensor reported by van der Heiden et al 52 .…”
Section: Discussionmentioning
confidence: 99%
“…22,31 The use of multiple (or array-type) sensors will further increase the accuracy as the three-dimensional dose distributions can be obtained using iterative time-reversal reconstruction methods. 20,32,33,34 Particularly, a novel array OH sensor reported by van der Heiden et al 52 is expected to realize the very accurate localization of BP with a minimal footprint. This line of research will significantly enhance the possibility of realizing IA range verification in clinics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations